MENANAMKAN NILAI KEARIFAN LOKAL MASYARAKAT SUNDA KEPADA ANAK-ANAK “Kinderdorf” LEMBANG - Dian Indira; R M Mulyadi; Hilman Fauzia (Bajang Institute, 2022)
Society develops dynamically in accordance with the times, as is the case in West Java, which currently has a heterogeneous society. Living in a heterogeneous environment requires speaking in a language that is equally understood between speakers, so it cannot be denied that the possibility of shifting Sundanese culture/language as the language of the Sundanese people cannot be denied. Children are the hope for the preservation of Sundanese language and culture, so that the Sundanese language/culture can continue to be inherited. Community service activities (PKM) carried out in